(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
Cambrian to Lower Ordovician acritarchs and Lower Ordovician conodont species have been recorded from the Furuhäll Section at Köpingsklint on Öland, Sweden. The acritarchs are represented by three different microfloras. The first is found at the base of the section investigated and is characterized by the association of Cristallinium cambriense with Eliasum llaniscum, Retisphaeridium dichamerum and R. howellii. This microflora has been recorded in strata previously referred to the Paradoxides paradoxissimus trilobite Superzone. The second microflora includes Timofeevia lancarae, T. pentagonalis and T. phosphoritica and it has been found in layers dated to the Upper Cambrian Agnostus pisiformis trilobite Zone. The third microflora comprises Of several species among which Aremoricanium ? grootaertii, Athabascaella playfordii, Dasydiacrodium tremadocum, Stelliferidium furcatum which are indicative of a Tremadocian age. This association includes taxa which usually occur in different bioprovinces, thus it allows transprovincial correlations. This microflora has been recorded in Lower Ordovician (Tremadocian) strata Of the Dictyonema flabelliforme s.l. - Clonograptus heres graptolite Zones. The new species Adara (Middle Cambrian) and Cristallinium aciculatum (Upper Cambrian) are described. The conodont species are referable to Tremadocian Paltodus deltifer Zone and Paroistodus proteus, Prioniodus elegans and Oepikodus evae conodont Zones Of the Arenigian. The fauna is typical Baltic, but includes elements of Tropodus and Tropodus sweeti which otherwise are known from the midcontinent conodont faunal province. The composition of the multielement species Baltonidius ? deltatus, B. crassulus, Oistodus aff. O. lanceolatus, Paltodus deltifer, P. peracutus and P. subaequalis is revised. The sequence of Furuhäll is characterized by several hiata, some of which can be related to eustatic sea level lows. The most extensive hiatus is from the Upper Cambrian Leptoblastus trilobite Zone into the early Tremadocian Dictyonema flabilliforme s.l. Zone. Barren interzones have been recorded at the base and at the top of Hunnebergian Substage. The lower barren inter-zone corresponds to the Tremadocian - Arenigian stage boundary or the Paltodus deltifer - Paroistodus proteus zonal boundary. The upper barren interzone coincides With Paroistodus proteus and Prioniodus elegans zonal boundary.